2016
DOI: 10.1188/16.onf.86-92
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Shared Decision Making About Prostate Cancer Screening Among African American Men

Abstract: Nurses can play a meaningful role in collaborating with community lay leaders to develop and implement effective health promotion interventions for African Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…However, the modest gain in this pilot provides the impetus to implement a larger scale intervention with longer and more in-depth educational sessions as recommended by the participants. Similar to this study, several studies have demonstrated the effectiveness of community-engaged health education in increasing knowledge of CVD (Brewer et al, 2017;Daniels et al, 2012), mental health (Ann Hall et al, 2011;Fuller et al, 2012), diabetes (Bertera, 2014;Embry et al, 2013;Peña-Purcell et al, 2015), and prostate cancer (Boehm et al, 1995;Linnan et al, 2014;Sandiford & D'Errico, 2016) among African Americans. A critical element is the utilization of existing social institutions and structures in the AA community to implement these health promotion programs.…”
Section: Increase In Knowledge and Awarenesssupporting
confidence: 76%
“…However, the modest gain in this pilot provides the impetus to implement a larger scale intervention with longer and more in-depth educational sessions as recommended by the participants. Similar to this study, several studies have demonstrated the effectiveness of community-engaged health education in increasing knowledge of CVD (Brewer et al, 2017;Daniels et al, 2012), mental health (Ann Hall et al, 2011;Fuller et al, 2012), diabetes (Bertera, 2014;Embry et al, 2013;Peña-Purcell et al, 2015), and prostate cancer (Boehm et al, 1995;Linnan et al, 2014;Sandiford & D'Errico, 2016) among African Americans. A critical element is the utilization of existing social institutions and structures in the AA community to implement these health promotion programs.…”
Section: Increase In Knowledge and Awarenesssupporting
confidence: 76%
“…This suggests that merely encouraging screening is not sufficient and that SIDM with a discussion of the pros and cons of screening tailored to patients and their barriers is essential. 20,21 . Nurse practitioners and other providers make important contributions to initiating SIDM for PCa screening.…”
Section: Discussionmentioning
confidence: 99%
“…Essa não adesão relaciona-se a estereótipos de gênero caracterizadores da masculinidade hegemônica, cuja doença indica a fragilidade do corpo e, por consequência, do seu portador. Apesar de alguns homens se apresentarem mais acessíveis ao exame do toque retal, ainda é necessária maior sensibilização em relação à promoção de sua saúde (10,18) . Um ponto essencial é a desmistificação de condições importantes, como as expressas pelo pensamento de que somente os homens com dor, ardor e desconforto ao urinar devem fazer este exame (item 8).…”
Section: Resultsunclassified